Isolated Cystic Lesion of the Callosal Genu after Traumatic Brain Injury - Kato, Toru; Okumura, Akihisa; Tsuji, Takeshi; Emi, Misugi; Natsume, Jun (Neuropediatrics, 2012)
We report the case of a 17-month-old infant who developed an isolated cystic lesion of the callosal genu as a unique lesion of traumatic axonal injury (TAI). Although one of the most common sites of TAI is the corpus callosum, there have been no reports describing the lesion seen in our patient. Brain computed tomography findings were normal on the day of the traffic accident. After 3 months, brain magnetic resonance imaging showed an isolated cystic lesion of the callosal genu that had the appearance of a cystic cavity. This lesion decreased in size 16 months later. The neuroimaging findings of this patient suggest that an isolated cystic lesion of the callosal genu could appear as a unique form of TAI in infants after traumatic brain injury (TBI), but it is nevertheless important to attend to such lesions in children with TBI.
Keywords: genu of corpus callosum; cystic lesion; traumatic axonal injury; traumatic brain injury